INTRODUKSI INDUKAN DAN ALIH TEKNOLOGI PEMBENIHAN LOBSTER AIR TAWAR (CERAX QUADRICARINATUS) PADA KELOMPOK MASYARAKAT DI KECAMATAN LADONGI KABUPATEN KONAWE TIMUR - Indrayani; Yusnaini; Muhammad Ramli; Zainuddin Saenong; Indriyani Nur (LP2M Universitas Hasanuddin, 2020)
Broodstock Introduction and Technology Transfer of Crayfish (Cerax quadricarinatus) Hatchery in the Community Groups in Ladongi Subdistrict, East Konawe RegencyAbstract. Crayfish is an introduced species that has the potential to be developed. However, Its development is hindered by the availability of the seeds. The aim of this activity was to transfer crayfish hatchery technology into two community groups in Ladongi Subdistrict, East Konawe Regency. These activities were conducted from 2017-2018. The forms of activities were hatchery extension/training, introduction of crayfish broodstocks, contruction of breeding ponds and hatcheries and evaluation of knowledge, skills, availability of production facilities and the ability of partners to produce caryfish seeds. The results showed that the knowledge level of participants based on indicators was 55-91%., from know nothing to know many things about crayfish. The skill level of participants based on indicators was 64-100%, from unable to be able to seed crayfish. Both groups are able to manage resources and produce seeds, and as crayfish suppliers. In addition to seed production, the groups also produce crayfish for consumption and for broodstocks. Keywords: Crayfish, hatcheries, technology transfer, community groups.Abstrak. Lobster air tawar (LAT) merupakan spesies introduksi yang potensi dikembangkan, namun terkedala pada ketersediaan benih.Kegiatan ini bertujuan mentransfer teknologi pembenihan LAT kepada dua kelompok masyarakat di Kecamatan Ladongi Kabupaten Kolaka Timur. Kegiatan direalisasikan tahun 2017-2018. Bentuk kegiatan yaitu penyuluhan/pelatihan pembenihan, introduksi indukan LAT, konstruksi kolam indukan dan pembenihan. Evalusi tingkat pengetahuan, keterampilan, ketersediaan sarana produki dan kemampuan mitra memproduksi benih LAT. Hasil kegiatan menunjukan bahwa, tingkat serapan pengetahuan peserta berdasarkan indikator yaitu 55-91%, dari tidak tahu menjadi tahu tentang LAT. Tingkat keterampilan peserta berdasarkan indikator 64-100 %, dari tidak bisa menjadi bisa membenihkan LAT. Kedua kelompok mampu mengelola sumberdaya dan memproduksi benih, sebagai penyuplaiLAT. Selain bentuk benih kelompok memproduksi LAT ukuran konsumsi dan indukan bertelur.Kata Kunci: Lobster air tawar, pembenihan, alih teknologi, kelompok masyarakat